Interrater reliability and discriminant validity of the deductive reasoning test. - Goverover Y; Hinojosa J (American Journal of Occupational Therapy)
OBJECTIVE: The purpose of this study was to determine the interrater reliability and discriminant validity of Toglia's Deductive Reasoning test for individuals with brain injuries. METHOD: Forty-two individuals with brain injuries and 51 participants without disabilities ranging in age from 18 to 84 years were given the Deductive Reasoning test three consecutive times. A between groups repeated measure design was used to examine differences between the two groups in performance of the Deductive Reasoning test across the three trials. RESULTS: An interclass correlation coefficient (ICC) was statistically significant, indicating good interrater reliability for participants without disabilities. A repeated measures analysis of variance (ANOVA) comparing performance across trials and between groups revealed a significant group main effect, F(1,91) = 52.68, p < .001, thus, participants with brain injuries performed significantly lower on the test than participants without disabilities. This analysis also revealed a significant increase in all participants' scores across trials, F(1.63, 148.67) = 35.094, p < .001. CONCLUSION: Findings confirm acceptable interrater reliability of the Deductive Reasoning test. Further, comparison of the performance of the two groups supports the discriminant validity of the Deductive Reasoning test for individuals with brain injuries. Thus, the Deductive Reasoning test was found to be an appropriate, valid, and reliable assessment tool for occupational therapists to assess deductive reasoning skills in individuals with brain injuries. Additional research is needed to continue to investigate the psychometric value of the Deductive Reasoning test so that clinicians and researchers can use it appropriately.